INFLUENCE OF THE ANGLE OF EARTH'S REFRACTION ON THE ACCURACY OF TRIGONOMETRIC LEVELING: Array - , С. М. (Municipal economy of cities. Series: «Economy science», 2018)
The article provides a list of literature and scientific papers that examine the accuracy of geodetic measurements, issues of errors and errors, as well as factors affecting the accuracy and the possibility of taking them into account when conducting various geodetic works. It is emphasized that only with trigonometric leveling is the influence of the angle of earth refraction on the accuracy of the measurements taken into account. The scheme of trigonometric leveling and the principles of conducting these works with the appropriate formula are given. The principles of forming and changing the angle of the earth's refraction are stated. The essence of this physical phenomenon and the factors that influence it are described. The scheme for determining the zenith distance is given, taking into account the influence of the angle of earth's refraction and the formula for determining the true zenith distance. The diagram shows the path of the sighting beam from the observer to the observed point and the physical process of curvature of the sighting beam. It is noticed that the distortion occurs to a greater extent in the vertical plane, and slightly affects the horizontal angles. Zenith distance this distortion changes very significantly. The degree of influence of refraction on the measurement of horizontal and vertical angles is analyzed. The angle of the earth's refraction has the highest magnitude per day in the morning, before sunrise in the morning. The smallest value and the smallest rate of change of the angle of earth's refraction occur in the afternoon. A table is given with average values of the Earth's refractive index established by scientists in this field. The value of the coefficient of terrestrial refraction for the European part of the planet, as well as the value of the error that can affect this coefficient and its limits are given. At the end of the article the conclusions are written, where the importance of taking into account the coefficient of terrestrial refraction when trigonometric leveling is indicated. The article is aimed at geodesic industry specialists who want to expand their horizons and improve their professional level. Keywords: trigonometric leveling, refractive index, theodolite, zenith distance, measurement accuracy.